The Effectiveness of Token Economy Counseling in Intervening Eye Contact and Sitting Behavior in Autistic Children at Sibolga State Special Needs School - Regita Amira Putri; Saiful Akhyar Lubis; Abdul Aziz Rusman (FKIP - Universitas Riau, 2026)
The low ability of children with autism to maintain eye contact and remain seated during learning activities often becomes a major obstacle in the classroom learning process. These behavioral limitations reduce focus, interaction, and learning effectiveness, as observed among autistic students at Sibolga State Special Needs School. This study aims to determine the effectiveness of token economy counseling in improving eye contact and sitting behavior in children with autism. The research employed a single-subject research (SSR) method using an A–B–A design, with data collected through direct observation during baseline condition 1 (A1), intervention condition (B), and baseline condition 2 (A2). During the intervention phase, subjects who received token economy counseling showed a significant improvement in eye contact and sitting behavior, achieving a very good category. Furthermore, the improvement persisted in baseline condition 2 (A2), indicating that the positive effects of the intervention remained even after the treatment was discontinued. Based on these findings, it can be concluded that token economy counseling is effective in improving eye contact and sitting behavior in children with autism and can be applied as a behavioral intervention strategy in special education settings.